THE EFFECT OF MANAGER'S KNOWLEDGE OF THE AVAILABILIIT OF MANAGEMENT ACCOUNTING INFORMATION SYSTEMS BASED ON ACIIVITIE - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
TJ,is study aims to obtniu results of interpretatiou of: (1) Tlte effect of 111a11ager's k11awledge on mm1nge111e11t acco1111ti11g i11formatio11 system towards 111a11ageme11t's ways of co11trolli11.g; (2) Tlte effect of wa11ageme11.t's ways to control towardsf) availabilityof 111n1tngeweut acco1111ting system fmsed on the activities; (3) Tl,e effect of mm,ager's knowledge nbo11t 111n,mge111e11t ncco1111tiug i11formatio11 system towards tlte availability of 111m1nge111e11t ncco111tting system based 011 nctivities tltro11glt ma11ageme11.t's ways to c01,.l as n11. i11.terve11i11.g variable. TIJis re earc/1 method is 11si11.g descriptive nndverifimtive h;pes. 11,e 1111it of n11nlysis i11 this study l's tlte nntio11al private co11u11ercinl ba1tk in North 11 mntm by acco1mti11g and fi.11m1ce 11m11nger as respo11.de11t. Descriptive a11alyzGere pe1formed to a11alyze tlte object of researd1. While the verificn.tio11 a1talyzes co11.d11cted to e:rnwiue tlte i11jl.11e11.ce of 111m1nger's k11owledge nbout tlte 111n11age111eut acco1111fi11g i11formafio11 system and styles of 11m11age111eut's control towards tlte nvnilnbility of activities bnsed OIL 111n11.nge111eut ncco1111ti1tg systems with Partin/ Lenst qunre (PLS) mmlytical methods. 17,e results of U,e researd1 shows that: (1) Mminger's k11.owlerlge of 111n11.age111eut acco1111.ti11g informntio11 systems sig11ificn1ttl-11e11ce the style of mm1ngerne1tt control; (2) Tl,e sh;le of J//(1//(1geme11t co11.trol